2010
DOI: 10.1016/j.physleta.2010.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Competition between paramagnetism and diamagnetism in charged Fermi gases

Abstract: The charged Fermi gas with a small Lande-factor g is expected to be diamagnetic, while that with a larger g could be paramagnetic. We calculate the critical value of the g-factor which separates the dia-and para-magnetic regions. In the weak-field limit, gc has the same value both at high and low temperatures, gc = 1/ √ 12. Nevertheless, gc increases with the temperature reducing in finite magnetic fields. We also compare the gc value of Fermi gases with those of Boltzmann and Bose gases, supposing the particl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…From figure 3(b) we can find that m increase with increasing of Landé factor g until approximates saturation at higher Ī. It indicates that the larger Ī the larger m for the identical value of Landé factor g, where the Landé factor denotes the intensity of the paramagnetism [19,20]. From figure 3(a) and 3(b), we can find that the enhance of ferromagnetism stimulates the increasing of paramagnetism.…”
Section: The Modelmentioning
confidence: 78%
See 1 more Smart Citation
“…From figure 3(b) we can find that m increase with increasing of Landé factor g until approximates saturation at higher Ī. It indicates that the larger Ī the larger m for the identical value of Landé factor g, where the Landé factor denotes the intensity of the paramagnetism [19,20]. From figure 3(a) and 3(b), we can find that the enhance of ferromagnetism stimulates the increasing of paramagnetism.…”
Section: The Modelmentioning
confidence: 78%
“…A similar treatment has been used to deal with the diamagnetism of scalar Bose gases [16,17,18]. We have extended it to further study the competition between diamagnetism and paramagnetism of charged spin quantum gases [19,20]. As far as FM interaction is concerned, it is shown that the meanfield theory is still effective in understanding the main physics of magnetism [12,14,15].…”
Section: The Modelmentioning
confidence: 99%
“…The paramagnetism and diamagnetism in charged Fermi gases are explored in Refs. [38][39]. The low-temperature expression of the Pauli paramagnetic sus-ceptibility of the ideal anyons has also been given in Ref.…”
Section: Introductionmentioning
confidence: 99%